Wild Medicinal Plants of Jaunsar-Bawar (Western Himalayas), Uttarakhand - II - Bisht, D. S.; Pundir, Y. P. S. (Indian Forester, 2008)
The paper reports 67 wild medicinal plants used by the natives of Jaunsar-Bawar (Western Himalayas), Uttarakhand.